The co-occurrence of lichen sclerosus et atrophicus and celiac disease - Karadag, Ayse Serap (Indian Dermatol Online J, 2014)
A 53-year-old female patient was admitted to our clinic for generalized hypo/hyper-pigmented, partially firm and sclerotic plaques with undefined borders. As the skin biopsy taken from the lesion was compatible with lichen sclerosus et atrophicus (LSA), the patient was treated with ultraviolet A1 (UVA1) treatment. Upon follow-up, she developed abdominal pain and diarrhea. Further investigation (including endoscopic and laboratory tests) showed signs consistent with celiac disease. After 30 sessions of UVA1 treatment, the skin lesions partially regressed. We present this case because the co-occurrence of LSA and celiac disease is very rare.